A escuta da família frente ao diagnóstico de autismo da criança - um estudo psicanalítico - Almeida, Maíra Lopes (2017)
This study aims to investigate the reverberations of the Autism diagnosis of the child to the family. Psychoanalysis constitutes the theoretical and methodological frame that supports this research. The investigative route was delineated from the construction of a clinical case. 21 counseling sessions were cut for the purposes of this study. This sessions happened with a family composed of the parental couple, the eldest son and Ícaro, diagnosed as autistic at 3 years of age. The forwarding to psychological care was done by a gastro pediatrician due to Ícaro‟s refusal to eat solid foods, echolalia and this diagnosis. The parents and/or the oldest brother were present in all the sessions. The case has highlighted the specifics that the diagnosis can be established with the family group. Marked by losses, the family draws to the melancholy and the isolation, inoculated at explicit conflict of the family psyche. Without elaborating the grief, the family presents a melancholy affective tone that enables the establishment of a particular relationship with the diagnosis of Ícaro. This appears in the group as a defensive barrier to suffering the losses experienced and helpless condition exposed after such traumatic losses. The psychoanalytic listening by the family allowed access to psychic diagnosis function and expand the scope of care for the suffering of the group. The research points to the importance of broadening the scope of attention to the symptom of child with the overcoming of the sentence and the diagnostic approach to the subject and family in your uniqueness.